Refleksi Moral dan Implikasi Etis dari LGBT, Aborsi, dan Euthanasia dalam Konteks Modern: Moral Reflection and Ethical Implications of LGBT Issues, Abortion, and Euthanasia in the Modern Context - Rudy Arianto Krikhoff (Journal of Religious and Socio-Cultural, 2024)
Social transformation in modern society presents significant challenges for the church in responding to moral and ethical issues, particularly those related to LGBT, abortion, and euthanasia. These issues not only challenge the church's established views on human dignity and God's authority over life but also demand deeper reflection within the context of Christian theology. This article aims to analyze the moral reflection and ethical implications of these three issues, with the goal of understanding how the church can respond to social changes without neglecting essential Biblical principles, while remaining relevant amidst the changing times. This study uses a qualitative method, involving theological literature review as well as interviews with church leaders. The literature review highlights contemporary theological perspectives on morality, love, and justice in relation to LGBT, abortion, and euthanasia. Meanwhile, interviews with church leaders provide practical insights into how moral teachings are applied in navigating social dynamics. The results of this study show that the church must adopt a balanced approach: upholding Biblical moral principles, such as love and respect for life, while also engaging in a more inclusive and compassionate dialogue with society. This approach allows the church to remain relevant in addressing moral and ethical issues in the modern era, without losing its theological integrity. Transformasi sosial dalam masyarakat modern membawa tantangan signifikan bagi gereja dalam merespons isu-isu moral dan etis, khususnya terkait LGBT, aborsi, dan eutanasia. Ketiga isu ini tidak hanya mengguncang pandangan gereja yang telah mapan tentang martabat manusia dan otoritas Tuhan atas kehidupan, tetapi juga menuntut refleksi yang lebih mendalam dalam konteks teologi Kristen. Artikel ini bertujuan untuk menganalisis refleksi moral dan implikasi etis dari ketiga isu tersebut, dengan tujuan memahami bagaimana gereja dapat merespons perubahan sosial tanpa mengabaikan prinsip-prinsip Alkitabiah yang esensial, namun tetap relevan di tengah perkembangan zaman. Penelitian ini menggunakan metode kualitatif, meliputi kajian literatur teologis serta wawancara dengan tokoh-tokoh gereja. Kajian literatur menyoroti pandangan teolog kontemporer tentang moralitas, kasih, dan keadilan dalam kaitannya dengan LGBT, aborsi, dan eutanasia. Sementara itu, wawancara dengan para pemimpin gereja memberikan perspektif praktis mengenai bagaimana ajaran moral diterapkan dalam menghadapi dinamika sosial. Hasil penelitian ini menunjukkan bahwa gereja harus mengambil pendekatan yang seimbang: mempertahankan prinsip-prinsip moral Alkitabiah, seperti kasih dan penghormatan terhadap kehidupan, sambil membuka dialog yang lebih inklusif dan penuh kasih dengan masyarakat. Pendekatan ini memungkinkan gereja tetap relevan dalam merespons isu-isu moral dan etis di era modern, tanpa kehilangan integritas teologisnya.